The Remission of Social Anxiety Disorder After Trauma: A Case Report of Posttraumatic Growth? - Hühne, Verônica; Vigne, Paula; de Menezes, Gabriela B.; Fontenelle, Leonardo F. (Frontiers in Psychiatry, 2021)
Posttraumatic growth (PTG) describes positive psychological change and improvement beyond one’s previous functioning. It manifests as a change of the perception of self, improvement in the relationship with others, and a better outlook on life. Despite consistent literature on the occurrence of PTG in healthy subjects, there is still a dearth of studies in people with pre-existing mental disorders, especially anxiety disorders. We report the case of a patient previously diagnosed with social anxiety disorder (SAD), whose symptoms remitted and life view improved after a traumatic event, illustrating a case of PTG. The trauma shattered the patient’s previous belief system, allowing the emergence of a new cognitive schema. Although PTG and symptom remission do not necessarily correspond to the same construct, we believe that these phenomena were related to each other in this case, probably because of a notable change in our patient’s underlying belief system.